Association of polycystic ovarian syndrome and metabolic syndrome in Tripura, India - Batra, Ipsita; Baidya, Jahar Lal; Pradhan, Mamata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: A total 4-11% of women in India are affected by PCOS. Studies show that incidence and prevalence is increasing. It is a constellation of metabolic and endocrine abnormalities with significant cost to quality and quantity of life. Aim of this study was to find out the association of metabolic syndrome with PCOS. Objectives of this study were identified subjects suffering from PCOS and measure strength of association of metabolic syndrome. Methods: Case-control study conducted in the department of Obstetrics and Gynaecology Agartala Government Medical College, Agartala, Tripura from January 2017 to June 2018. Fifty cases were diagnosed by Rotterdam criteria and 50 cases age matched controls were recruited. Hundred subjects underwent evaluation for metabolic syndrome according to ESHRE/ASRM criteria. Statistical analysis was done using SPSS 17.0. Results: Mean age was 19.4±3.5 years. Oligomenorrhea found in 42 out of 50 cases. Hirsutism found in 54% of cases. There is a statistically significant difference in weight, BMI and waist circumference among PCOS cases and controls. Hypertriglyceridemia was found to be significantly higher among PCOS cases. Fasting glucose and 2-hour OGTT were found to be statistically significantly different. No association was found between metabolic syndrome and clinical hyperandrogenism, but metabolic syndrome was significantly associated with higher BMI. BMI, Hip circumference and oral glucose tolerance test were independent predictors of polycystic ovarian syndrome. Metabolic syndrome was present in 34% of cases. The odds ratio of having metabolic syndrome in a case of PCOS is 5.92. Conclusions: Association between PCOS and metabolic syndrome is statistically significant. The two entities are intrinsically linked to each other and early identification of one may lead to the diagnosis and management of the other.